Formation of Civic Character Through Extracurricular Activities in Elementary Schools - Yanti, Nelmida (Berpusi Publishing, 2025)
Scout extracurricular activities are one of the activities that can help in forming students' character. Through these extracurricular activities, students can develop their cognitive, affective and psychomotor skills. Scouts also aim to shape students' character, leadership and sense of nationalism. Scouts also play an important role in the physical, mental, social and spiritual development of students. The author uses a library study research method by collecting data from various written sources. From various reference sources, the results obtained show that there is a connection or influence of Scouting extracurricular activities on the formation of student character. In this case, through various activities and things that students learn and the experiences they gain, they shape students' character naturally. Character education through scout extracurriculars requires good activity management so that student character formation can run effectively. In the modern era, scouts have an important role in developing students' patriotism, nationalism and talents. The main goal of scouts is to educate and develop teenagers to become good and useful young people. Through scouting activities, students can develop attitudes, values and skills that are important for forming a generation that is responsible, disciplined, hard working and loves the homeland.